1994
DOI: 10.1007/bf00228988
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine lesion of the rat prefrontal cortex impairs motor initiation but not motor execution

Abstract: We examined the effects of bilateral 6-hydroxydopamine (6-OHDA) lesions of the medial prefrontal cortex (PFC) in rats on motor initiation and execution in a simple reaction time task. Reaction times (RT) and movement times (MT) were measured in trained rats on four pre-and postoperative days. Animals with 6-OHDA lesions were selectively impaired on motor initiation as measured by a significant increase in RT on each postoperative day. Motor execution was intact postoperatively, since MT was not altered. Neuroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 39 publications
2
10
0
Order By: Relevance
“…Specifically, depletion of prefrontal cortex DA has been shown to cause deficits in movement initiation in a simple reaction time task (Hauber et al 1994) and a role for the frontal cortex has been proposed for deficits in reaction time observed in Parkinson's disease, as well (Berry et al 1999). In the present study, the animals with the largest striatal lesion sustained a 55% decrease in prefrontal DA, thus contribution of this structure to the impairments in this group of animals cannot be ruled out.…”
Section: Discussionmentioning
confidence: 55%
“…Specifically, depletion of prefrontal cortex DA has been shown to cause deficits in movement initiation in a simple reaction time task (Hauber et al 1994) and a role for the frontal cortex has been proposed for deficits in reaction time observed in Parkinson's disease, as well (Berry et al 1999). In the present study, the animals with the largest striatal lesion sustained a 55% decrease in prefrontal DA, thus contribution of this structure to the impairments in this group of animals cannot be ruled out.…”
Section: Discussionmentioning
confidence: 55%
“…Together, these findings provide support to our observation that rats subjected to a 6-OHDA infusion had an almost complete unilateral pDMS DA depletion. One caveat to note, however, is that we did not quantify the exact extent of the DA depletion, for example, by measuring striatal tissue levels of DA (Hauber et al, 1994). Thus, we cannot exclude that the extent of DA depletion induced in our present study differed from those quantified in previous studies using lower concentrations of 6-OHDA (Baunez and Robbins, 1999;Blandini et al, 2007;Brown and Robbins, 1991;Winkler et al, 2002).…”
Section: Histologymentioning
confidence: 55%
“…In addition to mnemonic and attentional functions, the rat FC is also involved in the contl-ol/pI-eparation of motor functions [5,9,25]. Moreover, it has been suggested that the shoulder region of the FC may be regarded as the pre-motor cortex in the rat [36].…”
Section: Discussionmentioning
confidence: 99%